Bibliometric Study on The Role of Management Accounting in Business Decision Making in the Manufacturing Industry - Loso Judijanto; Ernawaty Usman (Westscience Press, 2024)
This bibliometric analysis explores the evolving field of management accounting by examining the co-occurrence of keywords in the literature from the past two decades. Using VOSviewer, the study maps the interconnections between traditional and emerging themes within management accounting, revealing a significant shift from conventional practices to a broader focus that incorporates strategic decision-making, technological advancements, and sustainability concerns. The visualization highlights the central role of traditional terms like cost and financial management while underscoring the growing importance of big data, artificial intelligence, and environmental management. The findings illustrate the discipline's response to the complexities of modern business environments, emphasizing the need for management accountants to develop skills in strategic analysis, technology, and sustainability integration. The study not only provides insights into the thematic evolution of the field but also suggests directions for future research and the necessary adaptation of professional training and education in management accounting.